Meta-research publications in dentistry: a review - Faggion Junior, Clóvis Mariano; Listl, Stefan; Smits, Kirsten (European journal of oral sciences, 2021)
The present scoping review has the objective of providing an overview of meta-research in dentistry. A search of the PubMed database was performed for the period 11 October 2014 to 10 October 2019. Study selection and data extraction were performed independently by one author; prior to this, a random sample of 10% of the retrieved titles and abstracts were independently screened by two authors, achieving agreement of >80% on eligibility for initial inclusion, corresponding to good agreement. The following information was extracted from the full text of each article: meta-research area of interest; study design; type of studies evaluated in the meta-research; type of methodology used in assessment of the primary research; conflicts of interest reported; sponsorships reported; dental discipline; journal of publication; country of the first author; number of citations; and impact factor. A total of 7800 documents were initially retrieved. After analysis of the title/abstract and the full text of each article, and a snowballing procedure, 155 meta-research studies were identified and included. The ‘methods’ and ‘reporting’ meta-research areas were the most prevalent, with 73 (47%) and 61 (40%) studies, respectively. General dentistry, and orthodontics and dentofacial orthopaedics were the dental specialties with the greatest number/proportion of included studies with 45 (29%) and 28 (18%) studies, respectively. These findings may help to prioritize future meta-research in dentistry, consequently avoiding unnessecary investigations, and increasing the value of oral and dental research.
Gesehen am 31.03.2021